2004
DOI: 10.1001/archopht.122.10.1471
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Proton Beam Therapy for Circumscribed Choroidal Hemangiomas

Abstract: To evaluate the efficacy and safety of proton beam therapy for complicated circumscribed choroidal hemangiomas. Methods: The study was a retrospective nonrandomized investigation. Seventeen consecutive patients, referred to the Institut Gustave-Roussy, Villejuif, France, for circumscribed choroidal hemangioma associated with serous retinal detachment were studied. Each eye received a total dose of 20 cobalt gray equivalents (CGEs) delivered in 15-second fractions of 5 CGEs over 4 days. Functional tests include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…[65] EBRT treats the entire choroid with a homogeneous dose of radiation. [63] In the largest series of choroidal hemangiomas treated with EBRT, subretinal fluid resolved in 63.8% and visual acuity was stable or improved in 78% of patients. [66] Ritland et al reported tumor regression in all nine treated eyes with EBRT.…”
Section: External Beam Radiotherapymentioning
confidence: 89%
See 2 more Smart Citations
“…[65] EBRT treats the entire choroid with a homogeneous dose of radiation. [63] In the largest series of choroidal hemangiomas treated with EBRT, subretinal fluid resolved in 63.8% and visual acuity was stable or improved in 78% of patients. [66] Ritland et al reported tumor regression in all nine treated eyes with EBRT.…”
Section: External Beam Radiotherapymentioning
confidence: 89%
“…Plaque brachytherapy allows more targeted treatment of the hemangioma, minimizing radiation-induced side effects but the dose is not homogeneous with higher doses at the tumor base than the apex. [63,67] Plaque radiotherapy is usually used for choroidal hemangioma with extensive subretinal fluid in which PDT would not be advised. Low-dose treatment is sufficient using 20 Gy apex dose.…”
Section: Plaque Brachytherapymentioning
confidence: 99%
See 1 more Smart Citation
“…33 Radiation therapy remains a useful treatment modality for larger choroidal haemangiomas with extensive exudative retinal detachment that are not amenable to vPDT therapy. 39 There is, however, a risk of radiationinduced complications (cataract, radiation retinopathy and optic neuropathy). Diffuse choroidal haemangiomas associated with Sturge-Weber syndrome can be treated by vPDT therapy, 40 though radiation therapy may be required for more severe cases.…”
Section: Vpdt Treatment Protocolsmentioning
confidence: 99%
“…Previous reports have demonstrated the effectiveness of proton beam irradiation (PBI) for choroidal hemangioma with surgical localization of the tumor using tantalum rings [14,15,16,17]. The physical characteristics of a proton beam – which include minimal scatter, increased dose at the end of the range, and the extremely sharp falloff at the distal end of the beam – make it ideal for localized intraocular irradiation allowing for minimal exposure of surrounding normal intraocular and orbital structures.…”
Section: Introductionmentioning
confidence: 99%